‘Skirting heaven, skirting hell’: the maternal perspective of Catholic women on abortion and the recent restrictions in abortion law in Poland - Krotofil, Joanna (Culture and religion, 2020)
In this paper we explore how young Polish Catholic mothers navigate the dominant discourses on abortion in light of the recent tightening of legislation in Poland. We draw on theoretical considerations about the relationships between norms, subjectivity, agency and resistance and propose ‘maternal knowledge’ as a central concept for our analysis. Our data consists of twenty-eight in-depth interviews conducted with mothers who self-identify as Catholics. We demonstrate how individual women engage with the three authoritative knowledges on abortion, namely the legal framework, the teaching of the Catholic Church and the medical knowledge, and accept, reject or revise their main premises by mobilising the lived maternal knowledge. The results of our analysis challenge the widely shared identification of the Catholic faith with the ‘pro-life’ orientation and reveal the complexities and contradictions of individual stances, which are often inconsistent with the official teaching of the Church.